Jurisdiction Analysis of The Distribution of Integrity Children Out of Marriage as Substitute Heritages (Study of The Supreme Court Decision Number: 784 K/Pdt/2014) - Gagah Hotma Parulian Siregar; Widhi Handoko (Universitas Islam Lamongan, 2021)
Many problems regarding inheritance law occur due to distribution that is not in accordance with applicable regulations. In the Supreme Court Decision Number 784 K/Pdt/2014, the main research problems are: (1) How is the distribution of the inheritance of children out of wedlock as replacement heirs based on the Civil Code study of the Supreme Court's decision number: 784 K/Pdt/2014 . (2) Is the content of the Supreme Court's order Number: 784/Pdt/2014 concerning the distribution of the inheritance of children out of wedlock as replacement heirs appropriate or not according to the Civil Code. This type of research is normative juridical. The data used are secondary data, library study data collection and qualitative data analysis and deductive method conclusions. The conclusion of this decision study states that (1) the heirs to the inheritance of the Supreme Court decision study number: 784 K/Pdt/2014 are Dewina Tjandra, Trisnani Tjandra, Patty Tjandra, Sarina Tjandra, Arifin Tjandra, Ony Tjandra, and Fitri Tjandra . (2) The Supreme Court's decision Number 784 K/Pdt/2014 regarding the distribution of the inheritance of children out of wedlock as substitute heirs is not in accordance with Article 842 of the Civil Code.